2014
DOI: 10.1021/jp503402w
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface Charge Repulsion of Adsorbed H-Adatoms on TiO2(110)

Abstract: We have used noncontact atomic force microscopy (NC-AFM) and Kelvin probe force microscopy (KPFM) to directly visualize the presence of charged subsurface impurities on rutile TiO2(110). The subsurface charges add an additional electrostatic force between the sample and tip so that they appear as hillocks in the NC-AFM topography. Analysis of several subsurface defects in the same NC-AFM image reveals that the hillocks have discrete heights, which means that defects at different subsurface levels can be detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 51 publications
1
50
0
Order By: Relevance
“…In the image of TiO 2 surface with adsorbed H atoms ( Fig. 1(c)), individual H atoms that are adsorbed on O atoms are imaged [8][9][10]. In the image of a single PTCDA molecule, chemical structure inside the molecule can be resolved by Pauli repulsive force even at room temperature [11].…”
Section: IImentioning
confidence: 99%
“…In the image of TiO 2 surface with adsorbed H atoms ( Fig. 1(c)), individual H atoms that are adsorbed on O atoms are imaged [8][9][10]. In the image of a single PTCDA molecule, chemical structure inside the molecule can be resolved by Pauli repulsive force even at room temperature [11].…”
Section: IImentioning
confidence: 99%
“…31,32 In some regions, we could not detect defects at all, which is due to the influence of charged subsurface defects. 33 The ratio of the two aforementioned defects changed with time. At room temperature, residual water and hydrogen adsorbed continuously causing the accumulation of hydrogen adatoms on the surface.…”
Section: A Surface Of Rutile Tio 2 (110)mentioning
confidence: 99%
“…[22][23][24] In particular, a previous STM study has demonstrated that adsorption of Cl 2 molecules on TiO 2 (110) is suppressed in the vicinity of positively charged subsurface impurities. [22][23][24] In particular, a previous STM study has demonstrated that adsorption of Cl 2 molecules on TiO 2 (110) is suppressed in the vicinity of positively charged subsurface impurities.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are just a few reports available in the literature that concern the potential influence of extrinsic subsurface defects on the chemistry of well-characterized TiO 2 surfaces. [22][23][24] In particular, a previous STM study has demonstrated that adsorption of Cl 2 molecules on TiO 2 (110) is suppressed in the vicinity of positively charged subsurface impurities. [22] This observation has been attributed to a local increase in the effective electron affinity around the impurity (though no corresponding computational work has been carried out).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation